MARKETING STRATEGY FOR EASY SAVINGS REWARDS BSI PRODUCTS IN THE INDUSTRIAL ERA 4.0 (Case Study of Indonesian Sharia Bank KCP Tegal) - A.T. Handoko; A.F. Udin (PT. Hafasy Dwi Nawasena, 2024)
The purpose of this research is to determine the marketing strategy that will be used by BSI Wadiah Easy to Market Savings Products in the Industrial Age 4.0. This research method is a field study with a qualitative approach. Technology Data collection is done through observation, interviews and documentation. information about it the data obtained is reduced, information is displayed and conclusions are drawn from it. The results of a study at Bank Syariah Indonesia KCP Tegal show that the marketing strategy used is the 4P Marketing mix (product, price, place, promotion) in marketing BSI Easy Wadiah Industry 4.0 Age Savings products which can attract customers to open BSI Easy Wadiah savings accounts. at the Indonesian sharia bank Tegal KCP so there is growth every month. Banks In marketing products, there are controlling and inhibiting factors. There are still many customers who have not kept up with developments in the industrial 4.0 era. Therefore, it is impossible to maximize the convenience of the facilities provided by banks. Implications of this study can be used as a reference for marketing BSI Easy Wadiah Savings products in Industry 4.0. The marketing strategy used in marketing savings products It is easy for Wadiah BSI to use the BSI application in Industry 4.0 Mobile to make it easier for customers to open accounts online and perform other banking transactions.